Dakwah Melalui Poster Media Sosial Instagram - Awaludin, M.; Saefullah, Chatib; Sukayat, Tata (Tabligh: Jurnal Komunikasi dan Penyiaran Islam, 2023)
This paper aims to determine the presentation of da'wah messages through graphic design associated with its elements and the interpretation of da'wah messages distributed through the @jendelamuslim.id account poster. The method used in this study is a descriptive method which intends to make an explanation of the events that occurred. Descriptive research has the aim of creating a structured, objective and accurate explanation of the phenomena and characteristics of a particular society or group. Research shows that almost all of @jendelamuslim.id contains elements of graphic design including: line, shape, texture, dark and light, size, color, typography, and has the principle of visual communication: balance and unity. Da'wah messages contained in the @jendelamuslim.id Instagram account are messages that contain messages of faith, worship, and morals.